Validación del uso de ems (etil metasulfonato) en alfalfa (medicago sativa) a condiciones tropicales. - Cadena Morales, Leila Isabel (2022)
The feeding of animals in the tropics is affected by food deficiency in dry and very rayni seasons, which results in a high percentage of decrease in their productivity, causing serious economic losses and even the death of animals of production. The present bibliographic review work is elaborated taking data from research project approved by the Technical University of Babahoyo with the topic validation of the use of EMS (Ethyl Metasulfonate) in alfalfa (Medicago sativa) under tropical conditions. Ethyl Metasulfonate is a chemical compound with mutagenic and teratogenic properties, that is, ability to produce point mutations by nucleotide substitution, especially by guanine alkylation. With the use of this mutagenic, the adaptation time of the alfalfa seed was reduced, which made it possible to carry out the research project. Alfalfa is a legume used animal feed due to its protein content of 22%, digestibility of up to 70%, dry matter 18%, moisture up to 82%, dry matter 18% and energy up to 20% which makes this legume an excellent source for animal nutrition. As results, it was obtained that the adaptation of Alfalfa (Medicago sativa) in the tropics with the use of EMS was carried out successfully, having higher germination than the national seed.